Ramanujan's papers - Ramanujan Aiyangar; Venkatachala, B J; Vinay, V; Yogananda, C S (Bangalore : Prism Books, 2000)
Collected papers of Srinivasa Ramanujan Aiyangar, 1887-1920, an Indian mathematician.
Includes bibliographical references.
Keywords: Mathematicians